Development of a strategic approach for comprehensive detection of organophosphate pesticide metabolites in urine: Extrapolation of cadusafos and prothiofos metabolomics data of mice to humans. Issue 1 (29th March 2021) - Nomasa, Karin; Oya, Naoko; Ito, Yuki; Terajima, Takehito; Nishino, Takahiro; Mohanto, Nayan Chandra; Sato, Hirotaka; Tomizawa, Motohiro; Kamijima, Michihiro
Abstract: Objectives: The comprehensive detection of environmental chemicals in biospecimens, an indispensable task in exposome research, is advancing. This study aimed to develop an exposomic approach to identify urinary metabolites of organophosphate (OP) pesticides, specifically cadusafos and prothiofos metabolites, as an example chemical group, using an original metabolome dataset generated from animal experiments. Methods: Urine samples from 73 university students were analyzed using liquid chromatography–high‐resolution mass spectrometry. The metabolome data, including the exact masses, retention time (tR ), and tandem mass spectra obtained from the human samples, were compared with the existing reference databases and with our original metabolome dataset for cadusafos and prothiofos, which was produced from mice to whom two doses of these OPs were orally administered. Results: Using the existing databases, one chromatographic peak was annotated as 2, 4‐dichlorophenol, which could be a prothiofos metabolite. Using our original dataset, one peak was annotated as a putative cadusafos metabolite and three peaks as putative prothiofos metabolites. Of these, all three peaks suggestive of prothiofos metabolites, 2, 4‐dichlorophenol, 3, 4, 5‐trihydroxy‐6‐(2, 4‐dichlorophenoxy) oxane‐2‐carboxylic acid, and (2, 4‐dichlorophenyl) hydrogen sulfate were confirmed as authentic compounds by comparing their peak data with both the original dataset and peak data of the standard reagents. The putative cadusafos metabolite was identified as a level C compound (metabolite candidate with limited plausibility). Conclusions: Our developed method successfully identified prothiofos metabolites that are usually not a target of biomonitoring studies. Our approach is extensively applicable to various environmental contaminants beyond OP pesticides.